Determining Eustachian Tube Function in Mucosal Ear Disease Using Cost-Effective, Consistent, Constant, Convenient Tests: A Hospital Based Study - Sphoorthi Basavannaiah (The Turkish Journal of Ear Nose and Throat)
Objective: Using a range of methods, the aim of this study was to measure the patency of the eustachian tube for its effectiveness in all cases of mucosal ear disease. The eustachian tube plays a pivotal role connecting the middle ear with the nasopharynx. It preserves the equilibrium between the middle ear and the outer air and protects the ear from various nasopharyngeal pressure changes, mounting secretions and microorganisms. Healthy eustachian tube functions and patency are prerequisites for effective graft uptake and successful tympanoplasty. The most common reason behind failure of graft uptake is abnormal function of the eustachian tube, where mucosal ear disease is present in the main pathology. Materials and Methods: 100 patients in the ENT OPD of the Subbaiah Institute of Medical Sciences, Shivomogga, were selected and screened and their tubal function was evaluated and equated with a few tests. Results: The results were tabulated based on 5 tests: Valsalva maneuver, siegalisation test, ear drops test, nasopharyngoscopy and tympanometry to which all selected patients were subjected. The outcomes were tabulated accordingly. Conclusion: Of all the tests carried out in this study, Toynbee was the only test which was accurate regarding the function of the eustachian tube as an opening and closing mechanism for the regulation of air pressure in the middle ear.